2021
DOI: 10.24127/ajpm.v10i2.3087
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Soal Hots (High Order Thinking Skill) Pada Siswa SMP Kelas Vii

Abstract: Tujuan penelitian ini adalah menganalisis kualitas butir soal HOTS pada peserta didik SMP kelas VII. Jenis penelitian yang digunakan adalah penelitian pengembangan. Penelitian pengembangan terdiri dari tahap pendefinisian, perancangan, pengembangan, dan diseminasi. Penelitian ini hanya sampai tahap pengembangan, lebih tepatnya sampai analisis kualitas butir soal HOTS. Analisis soal bertujuan untuk menghasilkan soal valid dan reliabel, serta dapat mengidentifikasi soal. Penilaian hanya terbatas pada aspek keter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Meanwhile, for the quality, it was in a good category. Therefore, the four problems can be used to evaluate grade VII learners (Aviory & Susetyawati, 2021). The study found that the test instrument to measure Higher Order Thinking Skills (HOTS) is oriented to the Programme for International Student Assessment (PISA) in Learners.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, for the quality, it was in a good category. Therefore, the four problems can be used to evaluate grade VII learners (Aviory & Susetyawati, 2021). The study found that the test instrument to measure Higher Order Thinking Skills (HOTS) is oriented to the Programme for International Student Assessment (PISA) in Learners.…”
Section: Introductionmentioning
confidence: 99%